Optimal selection of joint impoundment schemes of Xiluodu–Xiangjiaba–Three Gorges cascade reservoirs at the end of flood season. Issue 13 (19th January 2018) - Jun, Lu; Hongjie, Yu; Jiajie, Wu; Xiaoran, Yan; Changming, Ji
Abstract : To address conflicts between flood control and utilisation benefits in reservoir operation, this study takes Xiluodu–Xiangjiaba–Three Gorges cascade reservoirs as an example and selects their optimal impoundment schemes at the end of flood season by means of multi‐objective assessment and decision making. Firstly, on the basis of analysing the cascade reservoirs' impoundment situation, this study sets an impounding operation target and draws up preliminary impoundment schemes. Then each scheme is operated with typical flood data and a long series of runoff data. Secondly, based on the operation results, structural equation model is used to analyse flood control and benefit objectives, among which the mutual feedback relationship is revealed. Finally, given the correlation among different objectives and indexes, grey target model with positive and negative bull's‐eyes based on Mahalanobis distance is applied to assess each scheme, obtaining satisfactory solutions and thus picking out the optimal scheme, which can provide scientific reference for the actual operation of cascade reservoirs at the end of flood season.